History Curriculum, Geschichtsdidaktik, and the Problem of the Nation - Robert J. Parkes; Monika Vinterek (MDPI AG, 2012)
The field of curriculum studies has become increasingly sensitive to the "effects of global flows, transnational connections, and transcultural interactions" ([1], p. 43), and an international dialogue has begun to take shape between the European bildung-influenced tradition of Didaktiks and the Anglo-American psychologised Curriculum Studies tradition. As it stands, the dialogue has concentrated on a comparative analysis of the traditions at the level of general curriculum theory or Allgemeine Didaktik (see for example, [2]), and has rarely, if ever, drilled down into an area of subject-specific pedagogy or fachdidaktiks. This special issue seeks to address this directly, by encouraging a dialogue between various regional and national traditions of history education or Geschichtsdidaktik. [...]